Effects of ambient air pollution from municipal solid waste landfill on children's non-specific immunity and respiratory health. (May 2018) - Yu, Yunjiang; Yu, Ziling; Sun, Peng; Lin, Bigui; Li, Liangzhong; Wang, Zhengdong; Ma, Ruixue; Xiang, Mingdeng; Li, Hui; Guo, Shu
Abstract: This cross-sectional study investigated the association between air pollutant (AP) and respiratory health of 951 children residing near a municipal solid waste (MSW) landfill in Northern China. Results showed that students in non-exposure areas had significantly higher levels of lysozyme, secretory immunoglobulin A (SIgA), and better lung capacity than students in exposure areas ( p < .05). Multiple regression model analysis indicated that lysozyme levels exhibited a consistent negative association with methane (CH4 : β = −76.3, 95% CI –105 to −47.7) and sulfuretted hydrogen (H2 S: β = −11.7, 95% CI –20.2 to −3.19). In addition, SIgA levels were negatively associated with H2 S (β = −68.9, 95% CI –97.9 to −39.9) and ammonia (NH3 : β = −30.3, 95% CI –51.7 to −8.96). Among all AP, H2 S and sulfur dioxide (SO2 ) were the most robustly related with reduced lung function. H2 S exposure was negatively associated with six lung function indices, 1-s forced expiratory volume (FEV1%), mean forced expiratory flow between 25% and 75% (MMF), maximum voluntary ventilation (MVV), and forced expiratory flow at 25%, 50%, and 75% of the pulmonary volume (FEF25, FEF50, FEF75); and SO2 was negatively associated with FEV1%, MVV, FEF25, FEF50 and FEF75. Our results suggested that AP exposure was negatively associated with more lung function parameters in boys than in girls. In conclusion, our findings suggested that children living adjacent to landfill sites were more likely to have deficient non-specific immunity and impaired lung function. Graphical abstract: Image 1 Highlights: Higher levels of lysozyme, SIgA, and better lung capacity were observed in students from non-exposure areas. Lysozyme was negative association with CH4 and H2 S, while SIgA was negatively associated with H2 S or NH3 . H2 S and SO2 were most robustly related with reduced lung function. AP exposure may influence lung function more in male than in female students. Children living adjacent to a landfill were more likely to have deficient non-specific immunity and impaired lung function. Abstract : Children living adjacent to landfill sites were more likely to have deficient non-specific immunity and impaired lung function.